2022
DOI: 10.1186/s12903-022-02324-w
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of a novel zinc-containing desensitizer CAREDYNE Shield for cervical dentin hypersensitivity: a pilot randomized controlled trial

Abstract: Background Recently, a novel zinc-containing desensitizer, CAREDYNE Shield, was developed. This new type of desensitizer induces chemical occlusion of dentinal tubules for desensitization and releases zinc ion for root caries prevention. Despite these features, its clinical effectiveness in the improvement of cervical dentine hypersensitivity remains to be elucidated. Thus, we aimed to evaluate the effectiveness of CAREDYNE Shield in patients with CDH. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Recent studies have demonstrated that new types of DAs have comparable desensitizing effects on dentine. These include nano-hydroxyapatite (n-HAp) [ 21 , 22 , 23 ], photobiomodulation therapy (PBM) with a low-level infrared laser [ 24 ], nano-sized carbonate apatite (n-CAP) [ 25 ], zinc-containing desensitizer [ 26 ], etc. Most of the DAs block the opening of the bulk of the dentinal tubules and make the dentinal surface smooth by filling the irregularities, thereby decreasing the sensitivity [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that new types of DAs have comparable desensitizing effects on dentine. These include nano-hydroxyapatite (n-HAp) [ 21 , 22 , 23 ], photobiomodulation therapy (PBM) with a low-level infrared laser [ 24 ], nano-sized carbonate apatite (n-CAP) [ 25 ], zinc-containing desensitizer [ 26 ], etc. Most of the DAs block the opening of the bulk of the dentinal tubules and make the dentinal surface smooth by filling the irregularities, thereby decreasing the sensitivity [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies report the application of n-HAp as biomimetic material for enamel reconstruction after tooth mineral component loss, thanks to its aforementioned unique remineralization potential [19][20][21][22][23][24][25][26]. N-HAp toothpaste showed promising results in DH management and post-bleaching-related sensitivity [27][28][29].…”
Section: Introductionmentioning
confidence: 99%